PENGARUH CARA BELAJAR TERHADAP PRESTASI SISWA PADA PEMBELAJARAN DARING DAN LURING SD NEGERI KASSI KOTA MAKASSAR - Irmayanti; Perawati Abustang; Eka Fitriana HS; Jusmawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Irmayanti, 2021.The Effect of Learning Methods towards Student’ Achievement in Online and Offline Learning at SD NegeriKassi Makassar.Supervised by Perawati Bte Abustang and Eka Fitriana HS. This study aims to determine the effect of learning methods on student’ achievementin Online and Offline Learning at SD NegeriKassi Makassar. This research used Ex Post Facto research with a quantitative approach. The research took place at SD NegeriKassi Makassar. The sample in this study was all students of class IV/A and IV/B consisting of 20 students in class IV/A and 20 students in class IV/B, total the total sampel is 40 students, while the technique of sample is simple random sampling. Data collection is a questionnaire, with data analysis using spss 21.0. The results of the descriptive shows that the analysis of the student learning method was very good category (65%), and student’ achievement was good category (60%). Inferential analysis results show that there is a positive influence on the way of learning on student achievement is online and offline learning at SD NegeriKassi Makassar with a sig value of 0.000<0,05. So, theoretically and empirically the findings of this study states that the learning methodshaveaffectsof student achievement in online and offline learning at SD NegeriKassi Makassar. Keywords:Learning Method, Student’ Achievement, Online and Offline Learning